Meaning in Life Mediates Between Emotional Deregulation and Eating Disorders Psychopathology: A Research From the Meaning-Making Model of Eating Disorders - Marco, Jose H.; Cañabate, Montserrat; Martinez, Cristina; Baños, Rosa M.; Guillen, Verónica; Perez, Sandra (Frontiers in Psychology, 2021)
Emotional dysregulation, age, gender, and obesity are transdiagnostic risk factors for the development and maintenance of eating disorders (EDs). Previous studies found that patients with ED had less meaning in life than the non-clinical population, and that meaning in life acted as a buffer in the course of ED; however, to the data, there are no studies about the mediator role of meaning in life in association between the emotional dysregulation and the ED psychopathology. Objective: To analyze the mediating role of meaning in life in the relationship between emotional dysregulation and the ED psychopathology in three samples with diverse risk factors for ED. Method: Sample 1, n = 153 undergraduate young women; sample 2, n = 122 participants with obesity; and sample 3, n = 292 participants with ED. Multiple mediation analysis was performed. Results: Sample 1: meaning in life showed a mediation effect between emotional dysregulation and the ED psychopathology (direct effect β = 0.390, p < 0.05) (indirect effect β = 0.227, p < 0.05), body satisfaction (direct effect β = −0.017, p < 0.05) (indirect effect β = −0.013, p < 0.01), and depression symptoms (direct effect β = 1.112, p < 0.001) (indirect effect β = 0.414, p < 0.001); sample 2: meaning in life showed a mediation effect between emotional dysregulation and binge eating and purging behaviors (direct effect β = 0.194, p < 0.01) (indirect effect β = 0.054, p < 0.05) and depression symptoms (direct effect β = 0.357, p < 0.001) (indirect effect β = 0.063, p < 0.05); sample 3: meaning in life showed a mediation effect between emotional dysregulation and the ED psychopathology (direct effect β = 0.884, p < 0.001) (indirect effect β = 0.252, p < 0.007), body satisfaction (direct effect β = −0.033, p < 0.05) (indirect effect β = −0.021, p < 0.001), borderline symptoms (direct effect β = 0.040, p < 0.001) (indirect effect β = 0.025, p < 0.001), and hopelessness (direct effect β = 0.211, p < 0.001) (indirect effect β = 0.087, p < 0.001). Conclusions: These studies suggest the importance of considering meaning in life as a variable in the onset and maintenance of ED.